(untitled) (Journal of Informatics Education and Research, 2025)
Purpose Purpose of the study is to identify the relationship between industrial relations and organizational development. Study has focused on the overall development of the industry. This development aspect has aligned with industrial relationship and organizational development. Design / Methodology / Opportunity Data collections have done with the different respondents like employee, trade union leaders, human resource managers etc. Data collected from the SME of automobile industries. Questionnaire designed are aim to identify the relationship with industrial relations and organizational development. Findings Inter relationship of organizational development and industrial relations related factors and its contribution for the development of organization and employees has identifies. Research Limitations The data collected from 16 nos of SME located in Pimpri Chinchwad area are covered. Practical Implications Organization has to design the policies for the development of industrial relations which will ultimately effect on the development of the industries. Originality / Value The study has uniquely conducted with different attributes of industrial relations and develops the inter linkage between them.